IN-SITU OBSERVATIONS OF INTERGRANULAR STRESS CORROSION CRACKING - Duff, J; Marrow, T (2009)
The development and validation of predictive models for intergranular stress corrosion cracking requires knowledge of short crack growth kinetics in response to mechanical driving forces. A new experimental method for in-situ observation of the early stages of crack growth during stress corrosion cracking, via full field Digital Image Correlation, is described and data for crack growth development are presented. Intergranular stress corrosion cracks were nucleated in sensitised 304 stainless steel under static uniaxial flexural deflection, within a potassium tetrathionate environment. High resolution optical images of a 2mm by 2mm area are recorded through the test solution during the experiment. The raw images show no observable cracking. However, the high sensitivity of digital image correlation allows small crack opening displacements to be detected. The derived strain map of the sample surface thereby enables imaging of the cracks. Surface cracks with lengths exceeding approximately 30μm can be observed. Post processing of the strain maps is then used to track the development of the cracks. Copyright © 2008 by ASME.